(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the present era, health of the structure is of great concern to avoid further hazards caused by deterioration of the structure. So due importance should be given to health aspect of a structure because health defines the long term performance of the structure. Health monitoring is the detection of the overall health of a structure, which includes cracking, spalling of concrete and anything which disturbs the utility of the structure. Many researchers are engaged in detection of cracks with the help of vibration analysis. This method of detection of cracks has been considered as an cost effective and reliable method of health monitoring. The effect of crack location and depth of crack on the natural frequencies and mode shapes has been reviewed in this paper.